Association of Biomarker Cutoffs and Endoscopic Outcomes in Crohn's Disease: A Post Hoc Analysis From the CALM Study. Issue 10 (27th February 2020) - Reinisch, Walter; Panaccione, Remo; Bossuyt, Peter; Baert, Filip; Armuzzi, Alessandro; Hébuterne, Xavier; Travis, Simon; Danese, Silvio; Sandborn, William J; Schreiber, Stefan; Berg, Sofie; Zhou, Qian; et al.
Abstract: Background: CALM was a randomized phase 3 trial in patients with Crohn's disease (CD) that demonstrated improved endoscopic outcomes when treatment was escalated based on cutoffs for inflammatory biomarkers, fecal calprotectin (FC), C-reactive protein (CRP), and CD Activity Index (CDAI) remission vs CDAI response alone. The purpose of this post hoc analysis of CALM was to identify drivers of treatment escalation and evaluate the association between biomarker cutoff concentrations and endoscopic end points. Methods: The proportion of patients achieving CD Endoscopic Index of Severity (CDEIS) <4 and no deep ulcers 48 weeks after randomization was evaluated according to CRP <5 mg/L or ≥5 mg/L and FC <250 μg/g or ≥250 μg/g. Subgroup analyses were performed according to disease location, and sensitivity analyses were conducted in patients with elevated CRP and/or FC at baseline. The association between endoscopic end points and biomarker cutoffs was performed using χ  2 test. Results: The proportion of patients who achieved the primary end point CDEIS <4 and no deep ulcers was significantly greater for those with FC <250 µg/g (74%; P < 0.001), with an additive effect for CRP <5 mg/L. The association of FC <250 µg/g with improved endoscopic outcomes was independent of disease location, although the greatest association was observed for ileocolonic disease. Fecal calprotectin <250 µg/g, CRP <5 mg/L, and CDAI <150 gave a sensitivity/specificity of 72%/63% and positive/negative predictive values of 86%/42% for CDEIS <4 and no deep ulcers 48 weeks after randomization. Conclusion: This post hoc analysis of CALM demonstrated that a cutoff of FC <250 µg/g is a useful surrogate marker for mucosal healing in CD. Abstract : A post hoc analysis of a phase 3 trial in Crohn's disease showed that a fecal calprotectin cutoff of <250 μg/g accurately classified mucosal healing at week 48 after randomization in a majority of patients.